2018
DOI: 10.1002/asi.24002
|View full text |Cite
|
Sign up to set email alerts
|

Which domains do open‐access journals do best in? A 5‐year longitudinal study

Abstract: Although researchers have begun to investigate the difference in scientific impact between closed‐access and open‐access journals, studies that focus specifically on dynamic and disciplinary differences remain scarce. This study serves to fill this gap by using a large longitudinal dataset to examine these differences. Using CiteScore as a proxy for journal scientific impact, we employ a series of statistical tests to identify the quartile categories and disciplinary areas in which impact trends differ notably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Likewise, high-impact articles-cited up to several hundred times-have appeared even in some of the Beall's List accounting journals with the lowest citation rates (Walters, 2022). From one perspective, we might argue that a higher citation rate for a Beall's List journal reflects favorably on the journal by demonstrating that it contributes to the literature despite the factors working against it-biases against OA journals, biases against authors and publishers in the developing countries where many such journals originate, poor index coverage, and authors' understandable reluctance to cite journals that have been publicly labeled as predatory (Albu et al, 2015;Asai, 2021;Berger and Cirasella, 2015;Frandsen, 2017;Nwagwu and Ojemeni, 2015;Shen and Bj€ ork, 2015;Xia et al, 2015;Yan and Li, 2018). From this first perspective, a relatively high citation count for an article in a Beall's List journal reveals that subsequent authors have identified it as a genuine contribution to the literature despite the many biases that make them inclined not to cite it.…”
Section: Citation Impact Of Predatory Journalsmentioning
confidence: 99%
“…Likewise, high-impact articles-cited up to several hundred times-have appeared even in some of the Beall's List accounting journals with the lowest citation rates (Walters, 2022). From one perspective, we might argue that a higher citation rate for a Beall's List journal reflects favorably on the journal by demonstrating that it contributes to the literature despite the factors working against it-biases against OA journals, biases against authors and publishers in the developing countries where many such journals originate, poor index coverage, and authors' understandable reluctance to cite journals that have been publicly labeled as predatory (Albu et al, 2015;Asai, 2021;Berger and Cirasella, 2015;Frandsen, 2017;Nwagwu and Ojemeni, 2015;Shen and Bj€ ork, 2015;Xia et al, 2015;Yan and Li, 2018). From this first perspective, a relatively high citation count for an article in a Beall's List journal reveals that subsequent authors have identified it as a genuine contribution to the literature despite the many biases that make them inclined not to cite it.…”
Section: Citation Impact Of Predatory Journalsmentioning
confidence: 99%
“…Piwowar et al (2018) study a cross section of 100,000 articles across many disciplines, attempting to control for quality by including article age and field variables. Li et al (2018) (see also related work by Yan and Li, 2018) study a panel of journals over time, allowing them to estimate the effect of a change in access status for a given journal compared with control journals that do not change access status over the period. This identification strategy may not hold quality constant because the contents of the journal changes over time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Atayero et al [10], presented data that compared the situation of open access and subscription-based journals. The perceived impact of journals has been classified into quartiles for impact and reliability analysis [11]. The authors affirmed that CS is a viable alternative to TELKOMNIKA ISSN: 1693-6930 ◼ Modified CiteScore metric for reducing the effect of self-citations (Hilary I. Okagbue)…”
Section: Introductionmentioning
confidence: 99%